Minimax Theorem and Nash Equilibrium - Ferreira, Manuel Alberto M. (2013)
Two important results in Economics, the Minimax Theorem and the Nash Equilibrium are presented together with their mathematical fundaments. The results are obtained in the field of Functional Analysis.